Enhancing self-regulated learning: the moderating role of social support in the relationship between authoritative parenting and student autonomy - Hamid, Ilham; Rahmatiah, St.; Suriati , Suriati; Amir, Marwati (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This study aims to investigate the influence of authoritative parenting style, social support, and self-regulated learning (SRL) ability in university students. The approach used is quantitative with a post-positivism view and ex post facto method. The research sample consisted of 80 early semester students at UIN Alauddin who were selected using the saturated sample method. Data were collected through a Likert scale-based questionnaire and analysed using SmartPLS version 4.0. The results showed that social support did not have a significant direct influence on SRL, with a coefficient (β) of 0.000 and a P-Value of 0.999, indicating that social support alone is not enough to improve SRL ability. However, authoritative parenting style had a significant influence on SRL with a coefficient of 0.627 and a P-Value of 0.000, indicating a strong positive relationship. This authoritative parenting style encourages students to be more independent, responsible, and more able to organise their learning independently. The interaction analysis shows that social support acts as a moderator that strengthens the relationship between authoritative parenting style and SRL. At high levels of social support, the positive impact of authoritative parenting style on SRL was greater, whereas at low levels of social support, this relationship weakened. In conclusion, social support strengthens the effectiveness of authoritative parenting style in improving SRL. Therefore, efforts to improve college students' SRL need to integrate adequate social support with a supportive parenting style. These findings provide implications for educational institutions and families in creating an environment that supports the development of students' self-regulation abilities in the early semesters.